O valor social gerado e percebido em empreendimentos econômicos socioinclusivos: Um estudo de múltiplos casos - Giehl, Pedro Roque (Universidade do Vale do Rio dos Sinos, 2014)
This thesis examines the way innovation and social entrepreneurship create value by fostering change in people’s realities and the lives, overcoming the conditions of multiple vulnerability and exclusion. This is a characterized and comparative study of three social inclusive economic organizations: CooperGet, CataVida and Rede Industrial de Confecção Solidária. These organizations were made possible by the active involvement of social entrepreneurs, respectively: entrepreneur, municipal public administration and civil society organization. The main purpose of this study is to analyze how the social value is generated and identify how it is perceived by the entrepreneurs and benefit participants. The research finds support in the academic centers of Innovation and Social Entrepreneurship and the economic and social theories aimed at promoting economic and social development in a comprehensive and sustainable manner, beyond rationality focused on self-interest. Such perspectives are based on classical and contemporary Economic Sociology, which identifies the society and the economy as mutually rooted and intertwined, as well as on the Social Economy, aimed at building economic and social solutions to the problems generated in the globalized and exclusionary economy market. The research was made through the primary and secondary data whose analysis was based on references of Content Analysis and complementarily in discourse studies, to observe demonstrations at the language level, as regards the senses and effects of meaning from social, cultural and historical aspects of the subjects and to think in their conditions of discursive production. The study results reveal 9 significant changes in reality and in the lives of participants, indicating complex and diverse processes of generation and perception of social value. However, there are still contradictory elements that hinder the new social practices, such as alienation, low self-esteem, dependency and opportunism, showing that the new habitus, the result of an awareness of emancipated individuals, may be a future in progress, with its challenges and contradictions, but for now, still reveal processes dependent on entrepreneurs agents.
Keywords: Empreendedorismo; Valor social; Inovação social; Empreendimento econômico socioinclusivo; ACCNPQ::Ciências Sociais Aplicadas::Administração